Legal Protection and HIV/AIDS Prevention for Child Victims of Sexual Abuse - Lidya Rahmadani Hasibuan; Chairuni Nasution; Laura Enggelina Br. Sianturi (International Journal of Society and Law, 2025)
Child victims of sexual abuse face serious risks of human rights violations and HIV/AIDS transmission. Child victims of sexual abuse are a highly vulnerable group to human rights violations and various serious impacts, both physical, psychological, and health, including the risk of HIV/AIDS transmission. This condition demands comprehensive legal protection and effective and sustainable HIV/AIDS prevention efforts. This study aims to analyze legal protection for child victims of sexual abuse and the HIV/AIDS prevention policies and mechanisms provided by the state. The research method used is normative legal research with a legislative and conceptual approach, supported by a review of primary and secondary legal materials. The results show that Indonesia has various laws and regulations governing child protection and HIV/AIDS prevention, but their implementation still faces various obstacles. The main problems include limited access to child-friendly health services, a lack of integration between law enforcement processes and medical services, and suboptimal psychosocial support for victims. Furthermore, coordination between relevant institutions is still weak, so that the protection provided does not fully meet the best interests of children. Therefore, strengthening regulations, increasing synergy between sectors, and adopting a child rights-based approach to legal protection and HIV/AIDS prevention for child victims of sexual abuse is necessary.